Capacity to work while depressed and anxious – a phenomenological study. (23rd January 2013) - Bertilsson, Monica; Petersson, Eva-Lisa; Östlund, Gunnel; Waern, Margda; Hensing, Gunnel
Abstract: Purpose : The aim was to explore experiences of capacity to work in persons working while depressed and anxious in order to identify the essence of the phenomenon capacity to work. Method : Four focus groups were conducted with 17 participants employed within the regular job market. Illness experiences ranged from symptoms to clinical diagnoses. A phenomenological approach was employed. Results : The phenomenon of capacity to work was distinguished by nine constituents related to task, time, context and social interactions. The phenomenon encompassed a lost familiarity with one's ordinary work performance, the use of a working facade and adoption of new time-consuming work practices. Feelings of exposure in interpersonal encounters, disruption of work place order, lost "refueling" and a trade-off of between work capacity and leisure-time activities was also identified. The reduced capacity was pointed out as invisible, this invisibility was considered troublesome. Conclusions : A complex and comprehensive concept emerged, not earlier described in work capacity studies. Rehabilitation processes would benefit from deeper knowledge of the individual's capacity to work in order to make efficient adjustments at work. Results can have particular relevance both in clinical and occupational health practice, as well as in the workplaces, in supporting re-entering workers after sickness absence. Implications for Rehabilitation: The reduced capacity to work due to depression and anxiety is not always understandable or observable for others, therefore, the rehabilitation process would benefit from increased knowledge and understanding of the difficulties afflicted individuals experience at work. Identifying tasks that contribute to "refueling" at work might enhance the success of the rehabilitation. Rehabilitation programs could be tailored to better address the inabilities that impact on the capacity to work when depressed and anxious.